If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (n + 4 + -7)(n + 4) = 30 Reorder the terms: (4 + -7 + n)(n + 4) = 30 Combine like terms: 4 + -7 = -3 (-3 + n)(n + 4) = 30 Reorder the terms: (-3 + n)(4 + n) = 30 Multiply (-3 + n) * (4 + n) (-3(4 + n) + n(4 + n)) = 30 ((4 * -3 + n * -3) + n(4 + n)) = 30 ((-12 + -3n) + n(4 + n)) = 30 (-12 + -3n + (4 * n + n * n)) = 30 (-12 + -3n + (4n + n2)) = 30 Combine like terms: -3n + 4n = 1n (-12 + 1n + n2) = 30 Solving -12 + 1n + n2 = 30 Solving for variable 'n'. Reorder the terms: -12 + -30 + 1n + n2 = 30 + -30 Combine like terms: -12 + -30 = -42 -42 + 1n + n2 = 30 + -30 Combine like terms: 30 + -30 = 0 -42 + 1n + n2 = 0 Factor a trinomial. (-7 + -1n)(6 + -1n) = 0Subproblem 1
Set the factor '(-7 + -1n)' equal to zero and attempt to solve: Simplifying -7 + -1n = 0 Solving -7 + -1n = 0 Move all terms containing n to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -1n = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -1n = 0 + 7 -1n = 0 + 7 Combine like terms: 0 + 7 = 7 -1n = 7 Divide each side by '-1'. n = -7 Simplifying n = -7Subproblem 2
Set the factor '(6 + -1n)' equal to zero and attempt to solve: Simplifying 6 + -1n = 0 Solving 6 + -1n = 0 Move all terms containing n to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1n = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1n = 0 + -6 -1n = 0 + -6 Combine like terms: 0 + -6 = -6 -1n = -6 Divide each side by '-1'. n = 6 Simplifying n = 6Solution
n = {-7, 6}
| y=0.5x+18 | | 11x-17x=x^2+6 | | y=3(x-a)(x+b) | | ln(x)-ln(x-8)=5 | | 104=8(r+5) | | 2x*1.25=x+6 | | lnx-ln(x-8)=1 | | 2/3y=14 | | 0.6(p-2)=0.4p+1.2 | | 0.6(p-2)=0.4p+12 | | Log(14)x=2 | | 2x+1=z | | 2x-10=3x-65 | | Y=-16t^2+424 | | -6x-3(2x-15)=45 | | 8cosx+12sinx=13 | | 3+4sin^2(x)=6 | | -2-3+2x=-8x | | 2(m-8)2+3=53 | | 1/2-3/7= | | 2x-9x-7=0 | | 625m^4-1= | | 2x^4-36=0 | | 35x^4+100x^3y-15x^2y^2= | | H(t)=16t^2+256 | | 5-2x=4x+23 | | x^2+6x-6+12=78 | | 4(2x+9)=-38+42 | | (8+7)*6-(3*4)= | | 3(2x-5)=x*x-15 | | x+71+2x+3=180 | | x+3x+48=180 |